Henry and Mudge and a very merry Christmas : the twenty-fifth book of their adventures - Rylant, Cynthia (Rylant, Cynthia. Henry and Mudge books., 2004)
At Christmastime Henry and his dog Mudge enjoy baked treats, visits from relatives, lots of presents, and each other.